Cannabis Hunger Games: nutrient stress induction in flowering stage – impact of organic and mineral fertilizer levels on biomass, cannabidiol (CBD) yield and nutrient use efficiency - Massuela, Danilo Crispim; Munz, Sebastian; Hartung, Jens; Nkebiwe, Peteh Mehdi; Graeff-Hönninger, Simone (Frontiers in Plant Science, 2023)
Indoor medicinal cannabis cultivation systems enable year-round cultivation and better control of growing factors. H, however, such systems are energy and resource intensive, generating a high carbon and water footprint. Nutrient recommendations highly vary in these cultivation systems. Abiotic stress like . Nnutrient deprivation during flowering can trigger nutrient translocation and modulate the production of cannabinoids, leading to a higher which might increase nutrient agronomic nutrient use efficiency, and thus, a more sustainable use of fertilizers. Given the importance of fertilization regimes for medicinal cannabis and the relative importance of N, P and K on plant growth, t. This experiment compares two fertilizer types (mineral and organic) applied in three dilutions (80, 160 and 240 mg N L -1 ) to evaluate the effect of nutrient deprivation during flowering on biomass, Cannabidiol (CBD) yield and nutrient use efficiency of N, P and K. This is the first study showing the potential to reduce fertilizer input while maintaining CBD yield of medicinal cannabis. Under nutrient stress, inflorescence yield was significantly lower at the final harvest, however, this was compensated by a higher CBD concentration, resulting in 95% of CBD yield using one-third fewer less fertilizer. The higher nutrient use efficiency of N, P, and K in nutrient-deprived plants was achieved by a larger mobilization and translocation of nutrients increasing the utilization efficiency of acquired nutrients. The agronomic nutrient use efficiency of CBD yield -for N and K - increased 34% for the organic fertilizers and 72% for the mineral fertilizers comparing the dilution with one-third less nutrients (160) with the highest nutrient concentration (240). Differences in CBD yield between fertilizer types occurred only at the final harvest indicating limitations in nutrient uptake due to nutrient forms in the organic fertilizer. Our results showed a lower acquisition and utilization efficiency for the organic fertilizer, proposing the necessity to improve either the timing of bio-availability of organic fertilizers or the use of soil amendments.